The role of Gut Microbiota and Probiotics in physical performance of athletes - Literature review - Skupińska, Olga; Wojtczak, Karolina; Antczak, Joanna; Kajka, Anna; Hamerska, Julia; Ruta, Damian; Bocianiak, Bogumił; Hamerska, Laura; Lipska, Julia; Fenrych, Urszula (Quality in Sport, 2024)
INTRODUCTION: The human gut microbiota is an extremely diverse and complex ecosystem that inhibits the mucous membranes of the intestines. It is probable that the microbiota, with its capacity to influence the immune system and establish the conditions required for metabolic and structural functions essential for maintaining homeostasis, may significantly affect the health, well-being, and performance of athletes. PURPOSE: The aim of the study is to present the current state of knowledge about the differences in athletes’ gut microbiota, how these changes affect their physical performance and uncover the mechanisms behind gut microbiota and probiotics in physical performance among population of athletes. MATERIAL AND METHODS: The following review was conducted using the articles from the Pubmed and Google Scholar databases, employing keywords related to gut microbiota, athletes, physical performance. We collected studies performed on populations of athletes, exploring different sport disciplines. CONCLUSIONS: Numerous studies have investigated the gut microbiota of athletes, emphasizing the impact of both training and diet. Athletes’ unique dietary regimens, including higher protein or carbohydrates intake, influence their gut microbiome, leading to enhanced performance. These findings uncover that diet diversity correlates with gut diversity, which is linked to metabolic benefits and a lean phenotype. Studies on rugby players, cyclists, and marathoners reveal that certain microbial species, like Prevotella and Veillonella, are more abundant in athletes and play significant roles in nutrient metabolism and exercise recovery. These findings suggest that the interaction between athletic lifestyle and the gut microbiota affects positively the metabolism of the host, by enhancing microbiota diversity, and increasing the abundance of beneficial bacteria.